Lecturer's Pedagogic Competence in Developing Student Learning at the National University - Suryono Efendi (Institute of Computer Science (IOCS), 2021)
The competence of lecturers determines the quality of the implementation of the Tridharma of Higher Lecturers. One of the elements of lecturer competence, namely pedagogic competence, lecturers plays a role in building student learning abilities by generating learning motivation that determines business improvement and learning success. Lecturers as an element with a very strategic position in the learning process, lecturer's pedagogic competence is an essential aspect of learning development. Therefore, how is the role and contribution of a lecturer's pedagogic competence to learning development? This study uses a qualitative approach using secondary data and primary data, with secondary data collection techniques obtained from references and data that have been previously processed. In contrast, preliminary data is obtained based on data from observations, interviews, and centralized discussions. The results of the research on the pedagogic competence of lecturers provide a massive role in the development of learning covering several aspects, namely: Acquainting oneself with the characteristics of pupils, with learning theories and educational concepts, Curriculum development, educational activities, and student potential growth Student communication, assessment, and evaluation.